2015
DOI: 10.9758/cpn.2015.13.2.194
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Quality of Life and Cognitive Functions, Anxiety and Depression among Hospitalized Elderly Patients

Abstract: ObjectiveOlder people seek not only a longer life, but also a better quality of life (QOL). Our aim was to find out the relationship between QOL and socio-demographic factors, social activities, cognitive status, depression and anxiety symptoms among medically ill and hospitalized elderly people in Turkey.MethodsTwo hundred forty three patients age 65 years or older were examined. The Socio-demographic Data Survey, the Mini Mental State Examination (MMSE), the Geriatric Depression Scale-short form (GDS-15), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
5
36
0
2
Order By: Relevance
“…Similar to Saracli et al and Helvik et al, we identified an association between quality of life and cognitive function [20,25]. Similar to the previous studies [5,20,25], our study found that participants who have a good quality of life for years have the least risk of low cognitive function, whereas those who have a poor quality of life for years, or a worsening quality of life, had the highest or a higher risk of low cognitive function. An interesting factor was found in the group of people whose quality of life had improved.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to Saracli et al and Helvik et al, we identified an association between quality of life and cognitive function [20,25]. Similar to the previous studies [5,20,25], our study found that participants who have a good quality of life for years have the least risk of low cognitive function, whereas those who have a poor quality of life for years, or a worsening quality of life, had the highest or a higher risk of low cognitive function. An interesting factor was found in the group of people whose quality of life had improved.…”
Section: Discussionsupporting
confidence: 91%
“…In older adults, quality of life can have an overall association on the deterioration of cognitive function, including personal, familial, and social factors [24,25]. In line with that, quality of life can be expressed as the mixture of intrapersonal and social normative elements in past, current, and future [13,20,25,26]. Among the elderly population, quality of life showed a linkage with their cognitive level [27,28].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is reported that there is a strong relation between lower quality of life and depression. (41) Mental conditions like depression are strong predictors of quality of life compared to physical disabilities (42). Literature review findings suggest an obvious and consistent connection between depression and quality of life in both community dwelling and institutional older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is reported to be a very important part of one’s well-being according to the World Health Organization [ 10 ], and the oral health-related quality of life shares a relationship with the general quality of life [ 11 , 12 ]. Several studies have explored ways to measure the oral health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%